2021
DOI: 10.1137/20m1314410
|View full text |Cite
|
Sign up to set email alerts
|

From Heterogeneous Microscopic Traffic Flow Models to Macroscopic Models

Abstract: We consider traffic flows described by conservation laws. We study a 2:1 junction (with two incoming roads and one outgoing road) or a 1:2 junction (with one incoming road and two outgoing roads). At the mesoscopic level, the priority law at the junction is given by traffic lights, which are periodic in time and the traffic can also be slowed down by periodic in time flux-limiters.After a long time, and at large scale in space, we intuitively expect an effective junction condition to emerge. Precisely, we perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…The introduction of randomness in traffic flow problems is natural and can be traced back to [21]. The micro-macro derivation of the LWR model from a random one on a single road was established in [19]. Here we prove the corresponding result for a bifurcation.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…The introduction of randomness in traffic flow problems is natural and can be traced back to [21]. The micro-macro derivation of the LWR model from a random one on a single road was established in [19]. Here we prove the corresponding result for a bifurcation.…”
Section: Introductionmentioning
confidence: 75%
“…We recall from [19] the definition of the homogenized velocities V k and homogenized Hamiltonians: V 0 is the inverse of the continuous increasing map defined on p0, v0 q by v Ñ E " p Ṽ 0 Z0 q ´1pvq ı . We note that V 0 is defined on p∆ min , E " p Ṽ 0 Z0 q ´1pv 0 q ı q.…”
Section: The Homogenized Velocities and Hamiltoniansmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, it is taken as 0.54. Lane change correction index: according to the above analysis, the accurate daily average traffic volume can not be calculated. Because in the analysis, a whole lane is divided into two independent roads, and the influence of vehicle lane changing between the two lanes is not considered 16 . As scheme (1) does not allow big cars to change to the small lane, but allows cars to drive out of the highway to the large lane, the biggest impact of lane changing mainly refers to the situation that cars use the large lane when they leave the highway, thus occupying the resources of the large lane.…”
Section: Smart Traffic Flow Data Processingmentioning
confidence: 99%
“…Analysis of traffic characteristics: The traffic flow models are mainly divided into two categories, macro and micro [41,42], and the propagation characteristics can also be revealed from these two perspectives. It has been found that [43] the traffic flow at the macro-level is highly random and volatile, and the global vehicle status can be grasped in real-time through the I-VICS.…”
mentioning
confidence: 99%